"Twice" --> 2 *
"sum of a number and 3" -> (n + 3)
"is the same as" --> =
"11 increased by the number" --> 11 + n
2(n + 3) = 11 + n
Distribute the 2 through the parentheses:
2n + 6 = n + 11
Get like terms together (subtract n and subtract 6):
2n - n = 11 - 6
Simplify:
n = 5
Checking:
The sum of 5 and 3 is 8.
Twice this is 16.
11 increased by 5 is 16, which is the same.
So the number is 5.
2006-11-15 06:52:13
·
answer #1
·
answered by Puzzling 7
·
1⤊
0⤋
The best way to tackle this problem is to break it apart.
Let x = number
"the sum of a number and 3" -> x + 3
"twice the sum of a number and 3" -> 2(x + 3)
"is" -> =
"11 increased by the number" -> 11 + x
Put it all together:
2(x + 3) = 11 + x
2x + 6 = 11 +x
x + 6 = 11
x = 5
Hope this helps.
2006-11-15 14:56:27
·
answer #2
·
answered by trina_r 2
·
0⤊
0⤋
The number is 15
2006-11-15 18:00:23
·
answer #3
·
answered by timing21 2
·
0⤊
0⤋
2(n+3) = 11+n
2n+6 = 11+n
n = 5
2006-11-15 14:52:22
·
answer #4
·
answered by romanwahoo 2
·
0⤊
0⤋
2(3+x)=11+x
6+2x=11+x
-x -x
6+x=11
-6 -6
x = 5
CHECK
2(3+5)=11+5
2(8)=11+5
16=16
2006-11-15 16:12:23
·
answer #5
·
answered by Baby-Bop 1
·
0⤊
0⤋
Let the unknown number be "x", and then set up the problem this way:
2(x+3) = 11+x
2x + 6 = 11+x
Take away 1x from each side, leaving...
x+6 = 11
x = 5
2006-11-15 14:56:12
·
answer #6
·
answered by Daniel M99 2
·
0⤊
0⤋
2(n+3)=11+n
2n+6=11+n
n=5
2006-11-15 14:52:51
·
answer #7
·
answered by igot4onit 2
·
0⤊
0⤋
Let x -= the number
2x + 3 = 11 + x
x = 8
2006-11-15 14:51:44
·
answer #8
·
answered by T 5
·
0⤊
2⤋
this is the equation:
2(x+3)=x+11
2x+6=x+11
2x=x+5
x+5
others have said 8 but that is not the twice the sum of a number and three. that is just twice a number plus three.
2006-11-15 15:07:45
·
answer #9
·
answered by asslpman 2
·
1⤊
0⤋
let the no be x
given
2x+3=x+11
adding -3
2x=x+8
adding -x
x=8
the no is 8
check
16+3=8+11
2006-11-15 14:53:36
·
answer #10
·
answered by raj 7
·
0⤊
0⤋